2022-RA-1274-ESGO Preliminary data about correlation between CA125 increase and recist progression in patients with relapsed ovarian cancer treated with maintenance PARP inhibitors or bevacizumab after response to platinum based chemotherapy. (20th October 2022) - Sabetta, Giulia; Saponaro, Costanza; Mangili, Giorgia; Bergamini, Alice; Cioffi, Raffaella; Galli, Federica; Grassi, Elisa; Pella, Francesca; Rabaiotti, Emanuela; Vasta, Francesca Maria; Candotti, Giorgio
Abstract : Introduction/Background: Scarce evidence supports Cancer Antigen 125 (CA125) as a reliable recurrence biomarker in patients affected by Ovarian Cancer (OC) on maintenance treatment with PARP inhibitors (PARPi) or Bevacizumab after response to platinum-based therapy.Our aim is to assess concordance between CA125 increase and Response Evaluation Criteria In Solid Tumours (RECIST) progression in these patients. Methodology: The study includes 109 patients affected by CA125-sensitive OC on maintenance treatment with Bevacizumab (group A) or PARPi (group B) for at least two months after complete/partial response to platinum-based therapy. 55 patients underwent PARPi, 54 Bevacizumab. Data were concordant if CA125 increased within a month from radiological progression; otherwise they were considered discordant. Results: 38 (34.9%) patients relapsed under maintenance treatment; 18 (47.4%) had recurrence with PARPi, 20 (52.6%) under Bevacizumab.In group A concordant cases were 12 (60%), discordant cases accounted for 8 (40%). In this last category of patients in half cases CA125 increased before radiological progression, while in the other half marker was permanently negative; CA125 never increased after radiological progression.In group B concordant cases were 7 (38.9%), discordant ones were 11 (61.1%). In this last category of patients in 4 cases (36.4%) CA125 increased after radiological progression, while in the other 7 (63.6%) CA125 was constantly negative; marker never increased before radiological progression. Conclusion: In patients treated with PARPi CA125 does not always correlate with disease progression; in fact, in cases of relapse highlighted with imaging techniques, marker remains within the normal range. This contrasts with what happens in patients treated with Bevacizumab.In conclusion, CA125 and imaging should always be evaluated together.